(untitled) (Research, Society and Development, 2021)
In the last decades there has been a significant increase in STIs among the population aged over 60 years. The objective was to evaluate the serological profile and social representations of syphilis in the elderly. To evaluate the serological profile of this group, the treponemal immunochromatographic test was performed. The tests were carried out on 133 participants, aged between 60 and 84 years of both sexes, with non-reactive results in 100% of cases. The social representations of syphilis for the elderly is that it is a dangerous disease, but some of the interviewees did not associate it as a disease. In addition, most of them list the use of condoms as a method of disease prevention, but with low adherence to use. Our results indicate that the elderly people are vulnerable to syphilis.